2016
DOI: 10.1007/s00464-016-5300-4
|View full text |Cite
|
Sign up to set email alerts
|

Tokyo Guidelines 2013 may be too restrictive and patients with moderate and severe acute cholecystitis can be managed by early cholecystectomy too

Abstract: Severity grading of AC is not the sole determinant of early LC. Patient comorbidity also impacts clinical decision. Confirmation in a larger cohort is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…of 149 patients, the authors similarly found that although severity grade was significantly associated with mean length of stay, it was not associated with either complications. From those results, they mentioned severity grading of AC was not the sole determinant of early LC . They also mentioned that AC patients with Grade III, who had not been admitted to the ICU can be regarded as suitable candidates for early LC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…of 149 patients, the authors similarly found that although severity grade was significantly associated with mean length of stay, it was not associated with either complications. From those results, they mentioned severity grading of AC was not the sole determinant of early LC . They also mentioned that AC patients with Grade III, who had not been admitted to the ICU can be regarded as suitable candidates for early LC.…”
Section: Discussionmentioning
confidence: 99%
“…On the question of Grade III, two Australian and Singaporean studies have suggested that even Grade III patients can safely undergo surgery . Kamalapurkar et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations